valiação de algumas propriedades físico-químicas, antioxidantes e sensoriais de iogurte elaborado com polpa de noni (Morinda citrifolia L.) e acerola (Malpighia emarginata DC.) - Moura, Andrezza Assis Cruz (Universidade Federal Rural do Semi-Árido, 2014)
Innovation in products elaboration is a constant purpose in the food industry in order to get differential quality attributes. For this, the development of new flavors fruit yogurt may be well received by consumers of the product, especially if these present some antioxidant properties. Thus, this study aimed to evaluate some physical and chemical properties, antioxidants and sensory of yogurt manufactured from noni pulp (Morinda citrifolia L.) and acerola (Malpighia emarginata DC.) pulp. For this, the following formulations were developed: F1- natural yogurt (control); F2 - yogurt with acerola pulp (2.5%); F3 - yogurt with noni pulp (2.5%); F4 - mixed yogurt with acerola pulp (1.25%) and noni pulp (1.25%); F5 - yogurt with acerola pulp (5%); F6 - yogurt with noni pulp (5%); F7 - mixed yogurt with acerola pulp (2.5%) and noni pulp (2.5%). The physical and chemical analysis (pH, titratable acidity, milk fat and protein), phenolic content, antioxidant activity and sensory analysis (consistency, acceptance and purchase intent) were carried out in yogurt. The data were evaluated by the Scott-Knott test and Friedman with probability of 5%. All yogurts showed physical and chemical quality according to the quality standard established by brazilian legislation. There was treatment effect on physical and chemical parameters, except to pH. The yogurts manufactured with only acerola (2.5% and 5%) obtained higher antioxidant activity (51.56% and 79.83%, respectively). There was treatment effect for the sensory attributes evaluated. The formulations F1, F2 and F4 obtained higher consistency. The yogurt with 5% noni obtained lower acceptance and purchase intention. The yogurts with noni 2.5% and 2.5% acerola obtained lower rejections. The yogurt manufactured showed acceptance similar to the natural yogurt. Thus, the new yogurt formulations show great commercial potential
Physical and chemical properties, antioxidants and sensory Evaluation of yogurt manufactured from noni (Morinda citrifolia L.) and acerola (Malpighia emarginata DC.) pulp
Keywords: Yogurt; fruits; Sensory evaluation; Antioxidants Substances; Milk; Iogurte; Frutos; Análise sensorial; Substâncias Antioxidantes; Leite; CIENCIAS AGRARIAS::ZOOTECNIA